Seismic Retrofit Screening of Existing Highway Bridges With Consideration of Chloride-Induced Deterioration: A Bayesian Belief Network Model - Tesfamariam, Solomon; Bastidas-Arteaga, Emilio; Lounis, Zoubir (Frontiers in Built Environment, 2018)
Vulnerability of seismically deficient bridges, coupled with their ageing and deterioration, pose significant threat to safety, integrity and functionality of the highway network that could result in significant risks to public safety, traffic disruption, and socio-economic impacts. Given the limited funds available for bridge retrofit, there is a need for an effective management strategy that will enable engineers to identify and prioritise the high-risk bridges for detailed seismic evaluation and retrofit. A practical risk-based preliminary seismic screening technique is proposed in this paper that enables to develop a ranking or prioritization scheme for seismically-deficient bridges. The complex interactions between seismic hazard, bridge vulnerability and consequences of failure are handled in a hierarchical manner. A Bayesian belief network based modelling technique is used to aggregate through the hierarchy and generate risk indices by accounting for chloride-induced corrosion deterioration mechanisms. The efficacy of the proposed method is illustrated on two existing bridges that are assumed to be located in high seismic zones and designed under different standards concerning their structural safety under seismic loads and durability performance.